Analisis Keterbacaan Teks Buku Ajar Bahasa Indonesia SMA Kelas X Kurikulum Merdeka Menggunakan Formulasi Grafik Fry - Ai Siti Nurjamilah; Sri Maryani; Shinta Rosiana (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
The readability of textbook texts is a crucial factor in learning effectiveness, particularly within the implementation of the Merdeka Curriculum, which emphasizes independent learning. This study analyzes the readability level of texts in Indonesian Language textbooks for Senior High School (SMA) Grade X under the Merdeka Curriculum using the Fry Graph Formula. A qualitative descriptive method was applied to 30 sample texts from three different textbooks used in schools across Tasikmalaya Regency, Tasikmalaya City, and Ciamis Regency. The results indicate that only 50% of the texts were appropriate for the Grade X level. Some texts were classified as too easy (suitable for elementary/lower junior high school levels), such as "Bunga Mawar" (The Rose) and "Hikayat Raja Budiman" (The Tale of the Wise King), while others were overly complex (exceeding the senior high school level), such as "Walabi" (Wallaby) and "Agus Salim". This mismatch potentially hinders the development of students' reading literacy, induces boredom or frustration, and contradicts the differentiation principle of the Merdeka Curriculum. Consequently, it is necessary to integrate readability analysis into textbook standardization processes, revise unsuitable texts, provide scaffolding support for complex texts, and enhance teacher capacity in differentiating materials. These recommendations support the improvement of literacy quality in line with the objectives of Merdeka Belajar (Freedom in Learning).